Widespread ingestion of synthetic micro-particles by geese across Great Britain and Ireland - Coughlan, Neil; Baker-Horne, Connie; Brides, Kane; Cunningham, Eoghan M.; Dick, Jaimie T.A.; Doyle, Susan; Green, Andy J.; Griffith, Rose M.; Lyne, Linda; McMahon, Barry J.; Petrek, Scott W.; Williams, Hannah M.; et al. (Wildfowl, 2025)
Scant consideration has been given to the ingestion of synthetic micro-particles (e.g. plastic particles such as micro-fibres and micro-fragments 0.5–5 mm in size) by non-marine waterbirds, such as geese, residing in coastal and inland areas. In the present study, we therefore assessed the occurrence of micro-particle ingestion for five goose species across multiple locations throughout the United Kingdom and Ireland. Micro-particle recovery was inclusive of synthetic micro-fibres and micro-fragments, as well as treated textile micro-fibres such as dyed cotton fibres. Goose faecal samples were collected opportunistically between May 2018 and October 2019. At least one micro-particle was detected in 46.5% of the samples (n = 809 samples in total; 0–21 micro-particles per sample), which were collected from Greater White-fronted Geese Anser albifrons (n = 31 samples; 41.9% yielded micro-particles), Greylag Geese A. anser (n = 256; 58.6%), Pink-footed Geese A. brachyrhynchus (n = 66; 42.4%), Canada Geese Branta canadensis (n = 298; 36.6%) and Barnacle Geese B. leucopsis (n = 158; 48.1%). Time of year and distance from the coast had significant partial effects on the abundance of micro-particles recovered, with fewer micro-particles recovered during winter months and from locations > 70 km from the coast. Overall, it appears that the ingestion of synthetic micro-particles is a widespread and frequent occurrence, albeit in low quantities, in different goose species. Further research is however needed to ascertain the extent of absorption and subsequent impacts of chemical contaminants derived from synthetic micro-particles and textile fibres, especially in relation to bird health and developmental life stages.